KONSTRUKSI POSITIVISTIK DALAM KAJIAN STATISTIK DAN STUDI ISLAM - Zainal (Qolamuna : Jurnal Studi Islam, 2022)
This article emphasises explicitly the construction of the positivistic paradigm developed by Auguste Comte and its contribution to statistical and Islamic studies. Positivism does not accept the inner experience as a source of knowledge (rejects metaphysics). According to positivism, actual knowledge is only an external, objective experience that can be tested by the senses and proven through observation. In its development, positivism is widely used in Islamic sciences, including Islamic studies. Hypothetical logic, on the analytical-demonstrative method, recognises regularity and causality behind every social and natural phenomenon. Therefore, Islam has accommodated various paradigms of thought. It is only the task of the next researcher to develop it further Keywords: positivistic, statistics, Islamic studies